2014
DOI: 10.1122/1.4901750
|View full text |Cite
|
Sign up to set email alerts
|

Build-up and two-step relaxation of internal stress in jammed suspensions

Abstract: We perform experiments on jammed suspensions of microgels with different constituent properties to determine their stress relaxation behavior on flow cessation. We observe that the stress relaxes through a two-step process: A rapid initial relaxation where internal stresses are trapped followed by a much slower decay. Trapped internal stresses are related to the solvent viscosity, particle elasticity, and volume fraction through a universal scaling. The second slower relaxation of the internal stress is charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 53 publications
9
54
0
Order By: Relevance
“…Despite of that the validity of the Delaware-Rutgers rule suggests that our mixtures are not characterized by large structural heterogeneities while being amorphous and characterized by very weak ageing. Figure 13.The stress values are normalized by p, the stress corresponding to the steady-state stress (plateau) measured at the long time limit of (t) in transient tests performed at different shear rates .The probed RG(cHS=0.01 %) and APS state (cHS=5 %) relax after 100 s: the accumulated stress due to translational and rotational strain-induced motion relaxes after 100 sun like hard sphere glasses or jammed microgel suspensions which are characterized by non-negligible residual stresses [81], [82], [83]. On the other hand, the DG state is characterized by stresses not fully relaxed after 100 s. Such finding suggests that particle softness is important in determining the full relaxation of accumulated stress in colloidal glasses and also indirectly confirms that DG state is dominated by the frustrated dynamics of hard particles (HS-like stars and collapsed soft stars).Moreover, it is worth mentioning that for high shear rates, DG samples were found to be mechanically instable: for cHS> 20 % wt edge fracture systematically occurred for shear rates higher than 0.5 s -1…”
Section: Iii2 Strain Amplitude Sweeps and Yieldingmentioning
confidence: 99%
“…Despite of that the validity of the Delaware-Rutgers rule suggests that our mixtures are not characterized by large structural heterogeneities while being amorphous and characterized by very weak ageing. Figure 13.The stress values are normalized by p, the stress corresponding to the steady-state stress (plateau) measured at the long time limit of (t) in transient tests performed at different shear rates .The probed RG(cHS=0.01 %) and APS state (cHS=5 %) relax after 100 s: the accumulated stress due to translational and rotational strain-induced motion relaxes after 100 sun like hard sphere glasses or jammed microgel suspensions which are characterized by non-negligible residual stresses [81], [82], [83]. On the other hand, the DG state is characterized by stresses not fully relaxed after 100 s. Such finding suggests that particle softness is important in determining the full relaxation of accumulated stress in colloidal glasses and also indirectly confirms that DG state is dominated by the frustrated dynamics of hard particles (HS-like stars and collapsed soft stars).Moreover, it is worth mentioning that for high shear rates, DG samples were found to be mechanically instable: for cHS> 20 % wt edge fracture systematically occurred for shear rates higher than 0.5 s -1…”
Section: Iii2 Strain Amplitude Sweeps and Yieldingmentioning
confidence: 99%
“…It is acknowledged that residual stresses (also sometimes referred to as "internal" stresses) result from history-dependent microstructural features that are frozen-in upon cessation of shear and generally decrease with the preshear rate or stress. Recent studies include polyelectrolyte microgels [71,72], colloidal gels [82,83,86] as well as colloidal glasses [4]. Numerical simulations of random jammed assemblies of non-Brownian elastic spheres have shown that residual stresses can be attributed to quenched angular distortions of the microstructure that slowly relax over time [71].…”
Section: B Residual Stresses In Soft Materialsmentioning
confidence: 99%
“…This already shows that the stress-relaxation behavior is non-universal and rather depends on the specific system studied [30], see also [31] for a detailed review. It is to be noted that the particle softness, in the above-mentioned experimental work, is varied by changing the particle-size [28], cross-link density [23], and the temperature [24,25]. Adjusting these parameters, however, affects both the particle-permeability as well as the elastic modulus [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The microstructure, during this solidification process, is not fully equilibrated and part of the stress introduced during preparation persists in the system. The non-zero trapped stresses are known as the residual or internal stress [22][23][24]. The relaxation of the internal stresses, as the microstructure strives to reach equilibrium, has been found to appreciably affect the rheological properties of the suspension [22,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation